Analisis Faktor Yang Menghambat Mahasiswa Untuk Menabung Di Bank Syariah (Studi Kasus Pada Mahasiswa Fakultas Syariah Institut Agama Islam Az-zaytun Indonesia) - Madaniah, Zahra; Iswandi, Irvan; Utami, Dewi (JUPE : Jurnal Pendidikan Mandala, 2023)
This undergraduate thesis studied about the factor which inhibited students to save money at Shariah Bank and students’ perception of Islamic banks. Background in this research was that there were still many students of Shariah Faculty IAI Al-AZIS who saved money in conventional bank, while at semester 5, students of Shariah Economy Law Study Program has taken course of Product and Theory of Shariah Banking that must be the consideration for students to move to Shariah Bank. The purpose of this research was to find out the students’ point of view on shariah banking and to analyze the factors which inhibit them to save money at shariah bank. This research employed qualitative approach with questionnaire technique and interview on students of shariah faculty IAI Al-AZIS to collect the research data. Data sources used in this research are primary data and secondary data. Data analysis in this studi was carried out through 3 stages that is data reduction, data presentation, and drawing conclusions. The result of this research showed that predominantly the students have positive point of view on shariah bank. They said that shariah bank is in line with Islamic teaching. However there were also students who argue that shariah bank is the same with conventional bank. The inhibition factors of students to save money at Shariah Bank were far location of shariah bank from where they live, knowledge factor, group reference facgtor, and promotion factor.